An SCN1B Variant Affects Both Cardiac-Type (NaV1.5) and Brain-Type (NaV1.1) Sodium Currents and Contributes to Complex Concomitant Brain and Cardiac Disorders - Martinez-Moreno, Rebecca; Selga, Elisabet; Riuró, Helena; Carreras, David; Parnes, Mered; Srinivasan, Chandra; Wangler, Michael F.; Pérez, Guillermo J.; Scornik, Fabiana S.; Brugada, Ramon (Frontiers in Cell and Developmental Biology, 2020)
Voltage-gated sodium (NaV) channels are transmembrane proteins that initiate and propagate neuronal and cardiac action potentials. NaV channel β subunits have been widely studied due to their modulatory role. Mice null for Scn1b, which encodes NaV β1 and β1b subunits, have defects in neuronal development and excitability, spontaneous generalized seizures, cardiac arrhythmias, and early mortality. A mutation in exon 3 of SCN1B, c.308A>T leading to β1_p.D103V and β1b_p.D103V, was previously found in a patient with a history of proarrhythmic conditions with progressive atrial standstill as well as cognitive and motor deficits accompanying structural brain abnormalities. We investigated whether β1 or β1b subunits carrying this mutation affect NaV1.5 and/or NaV1.1 currents using a whole cell patch-clamp technique in tsA201 cells. We observed a decrease in sodium current density in cells co-expressing NaV1.5 or NaV1.1 and β1D103V compared to β1WT. Interestingly, β1bD103V did not affect NaV1.1 sodium current density but induced a positive shift in the voltage dependence of inactivation and a faster recovery from inactivation compared to β1bWT. The β1bD103V isoform did not affect NaV1.5 current properties. Although the SCN1B_c.308A>T mutation may not be the sole cause of the patient’s symptoms, we observed a clear loss of function in both cardiac and brain sodium channels. Our results suggest that the mutant β1 and β1b subunits play a fundamental role in the observed electrical dysfunction.